Analysis of Stakeholders' Perception on The Quality of The Financial Information Reported by Companies from Emerging Countries - Anatol MELEGA; Veronica GROSU; Marian SOCOLIUC; Daniel BOTEZ (Communications of International Proceedings, 2022)
Each user of financial information has his own requirements regarding the content of the financial statements and the way they should be presented. Sometimes, in order to make a well-informed decision, the users of financial information ask also for other documents - in addition to the annual financial statements - to provide them with a wider range of knowledge about the company's situation. Thus, the quality of the information that is presented in the financial statements plays a key role in promoting global economic stability. In a world characterized by large and rapid international capital flows, transparency in providing accurate and timely economic data can reduce uncertainty and improve the ability of the market / investors to assess risks. The aim of this research is to analyse the perception on the quality of financial accounting information from the perspective of their users from emerging economies, using the method of the questionnaire.
Keywords: emerging economies; financial information; quality; IFRS; stakeholders.